Representation of Pakistani Culture through Code-Mixing: A Critical Analysis of the Novel Holy Woman by Qaisra Shahraz - Khan Muhammad zawar; Sardar Sana; Nazir Muhammad (Lingua Cultura, 2021)
The research aimed to analyze the characteristics of code-mixing in the novel The Holy Woman by Qaisra Shahraz and the repetition of Urdu words. Code-mixing was an unconscious process that established communication in a multilingual community. It would describe research design, data collection, reasons for accumulating data from the novel, models of linguistic features, and the contextual areas of South Asian English and data analysis. The research applied a qualitative method of analysis that probed the enormous data and detailed analysis of the novel to find out features of code-mixing, the native socio-cultural realities to show the lexical gap. The research depicted the ideologies related to a different culture in Pakistan through code-mixing and language use in the novel. The data had been analyzed through Baumgartner, Kennedy, and Shamim’s (1993) and Kachru’s (1983) model of code-mixing. The research finds that the writer spots the light on the regional varieties that sound more familiar to the readers and Pakistani English to fill the lexical gap because they sometimes do not find proper words in standard English. The writer has used the words frequently in the novel to actualize the inherent culture of society and describe socio-cultural realities. The research has found 400 words (English-Urdu words) in the thirty-two semantic contexts. The writer has mixed Urdu words with the English language where it is needed because of the contextual, cultural differences, social norms, values, beliefs, ideas, customs, and traditions of the society; and stress the importance of Pakistani English with distinct linguistic features.